Effects of Pregabalin as Preemptive Analgesia for Pain Score, Sedation Score, and Cortisol Level after Caesarean Section Under Spinal Anesthesia - Ahmad, Muhammad Ramli; Siradjuddin, Ardiansyah; Gaus, Syafruddin; Arif, Syafri Kamsul; Husain, Alamsyah Ambo Ala; Adil, Andi (Open Access Macedonian Journal of Medical Sciences, 2023)
INTRODUCTION: Cesarean section (C-section) is an increasingly common method of delivery, so optimal management of anesthesia and post-operative pain is essential for better outcomes. Preemptive analgesia is an effective method for preventing post-operative pain, with the benefits of pregabalin specifically being much studied and debated. This study aimed to determine the side effects and efficacy of different pregabalin doses for pain management and prevention of stress response in C-section patients under spinal anesthesia. MATERIALS AND METHODS: This double-blind randomized trial study examined 30 patients who underwent elective C-section under spinal anesthesia with 0.5% hyperbaric bupivacaine 10 mg + adjuvant fentanyl 25 mcg, who were divided into three equal groups which received oral placebo or pregabalin (75 or 150 mg). Pain scores, sedation scores, and cortisol levels and changes were analyzed, the former two using Mann–Whitney tests, cortisol levels using one-way Analysis of variance (ANOVA) tests, and cortisol level changes using repeated-measures ANOVA tests on SPSS software version 20. Results were considered significant when p < 0.05. RESULTS: There were significant differences in numerical rating scale between the placebo and pregabalin groups at rest and movement after surgery (p < 0.05), and in sedation scores between the placebo and 150 mg groups and between the 75 mg and 150 mg groups at 2 and 6-h post-surgery (p < 0.05), as well as cortisol level changes between all groups (p < 0.05). CONCLUSIONS: Preemptive administration of pregabalin 75 mg is recommended for C-section surgery because it may reduce post-operative pain with minimal side effects.